Efficacy of CMC supplementary burns feed (SBF) in burns patients: A retrospective study. Issue 1 (January 2020) - Kumar Gupta, Ashish; Mendiratta, Siddharth; Lamba, Shashank; Jayantilal Gohil, Amish; Gorka, Rahul
Highlights: Early enteral feeds aid in reducing weight loss and overall morbidity and mortality. Only four patients out of 40 (10%) had more than 10% weight loss. Our Supplementary Burns Feed is relatively cheap, palatable & easily reproducible. Abstract: Burn injury ensues catabolism that leads to a significant increase in the energy and protein requirements of the patient. To meet these demands, they need some other form of enteral formula diet along with a regular diet. At our centre, a hospital-based diet prepared by the dietary department was used for this purpose. The research aimed to examine the efficacy of this formulation post-burn nutritional support. Material and methods: This study was carried out in 40 patients with more than 20% TBSA burns who fulfilled the inclusion criteria, admitted in our burns centre from Jan 2011 to Dec 2016 and received hospital-based supplementary burns feed (SBF). They were studied based on the length of hospital stay, weight loss, serum prealbumin, and albumin levels, the number of surgeries, and other parameters. Results: Out of the 40 patients, 36 were able to maintain less than 10% weight loss with improvement in serum prealbumin levels and a direct correlation of weight loss with the duration of hospital stay. The serum albumin level was the same throughout the analysis and was deemed insignificant. Conclusion: Our hospital-based SBF is a palatable and cost-effective supplement to regular diet in countries with differences in medical treatment and cultures without requiring a technologically advanced environment.